A report of 12 cases of congenital hepatic hemangioma and literature review - Wei, Ying; Rong, Zhihui; Gao, Jinzhi; Chen, Ling (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the clinical features, complications, diagnosis and management of congenital hepatic hemangiomas(CHHs).Methods12 neonates of CHH admitted to our hospital in the past 10 years were retrospectively analyzed, and the clinical manifestations, auxiliary examination results, diagnosis and treatment methods, clinical efficacy andprognosis were reviewed.ResultsIn this study, 12 neonates with CHHs were reported. Among them, 8 cases underwent surgical treatment and recovered well postoperatively. 3 cases received routine pharmacological treatment, were gradually recovering. Only one case, presenting with giant CHH and congestive heart failure (CHF) at birth, failed initial pharmacological treatment and underwent percutaneous hepatic hemangioma embolization but died postoperatively.ConclusionLarge CHHs tend to be complicated with refractory congestive heart failure, likely due to tumor size and intra-tumor arteriovenous shunt. Propranolol is effective for CHHs with stable hemodynamics but has a slow onset of action, making it less suitable for cases complicated with CHF. Surgical resection is effective and recommended for large CHHs with stable hemodynamics, while percutaneous hepatic hemangioma embolization is advised for unstable cases.